Effect of Picture-Book Reading With Additive Audio on Bilingual Preschoolers’ Prefrontal Activation: A Naturalistic Functional Near-Infrared Spectroscopy Study - Li, Chuanjiang; Ding, Keya; Zhang, Mingming; Zhang, Li; Zhou, Jing; Yu, Dongchuan (Frontiers in Psychology, 2020)
Acquiring a second language (L2) has the power to shape cognition and even the function and structure of the brain. Picture-book reading with additive audio (PRA) is a popular and convenient means of providing L2 exposure for non-balanced bilingual children; however, its contribution to bilingual children’s brain activity is unclear. This study conducted a rigorous bilingual word comprehension experiment and a naturalistic PRA task to explore the effect of L2 processing on brain activation among English as a foreign language (EFL) preschoolers, using functional near-infrared spectroscopy (fNIRS). We found that the two contexts of comprehending English words and bilingual switching, which impose more cognitive control demands, activated the prefrontal cortex (PFC) more than did the condition of Chinese words comprehension. Furthermore, the effect of PFC activity in the condition of picture-book reading with additive English audio (English PRA) was also found to be greater than in the condition of picture-book reading with additive Chinese audio (Chinese PRA); moreover, the effect was modulated by story difficulty. Finally, a positive correlation was shown between EFL children’s English competence and PFC activation through English PRA. This study indicates that the experiences of hearing L2 auditory stories in picture-book reading activity yielded significant changes to early bilingual’s PFC functional for cognitive control and language processing.